Who is φυσικος According to Aristotle? (De an. 403A29-B18) - Stransky, Jiri (Aither, 2015)
The aim of this paper is to answer the following question: "Who, according to Aristotle, is the natural philosopher?" On the basis of a short passage from De anima (403a29-b18) it is argued that the term "natural philosopher" is used by Aristotle in two different senses: first, it applies to a ionian type of thinker who reduces his research to the material cause only, second, it applies to a thinker who does his research properly, that is, who takes into account all four aristotelian causes.